Interaksi Simbolik Kegiatan Reses di Wilayah Dapil 1 Tangerang Kota - Martin, Helice; Pribadi, Muhammad Adi (Koneksi, 2023)
Recess activities are two-way verbal communication between legislators and citizens to absorb the aspirations of the community directly to council members without intermediaries. Researchers examined symbolic interaction in recess activities held by the regional people's representative council (DPRD) members and attended by community members. This theory discusses how individuals think in an interaction in a social environment. There are mind, self, and society in symbolic interaction that plays an important role in ongoing social interaction. The methodology used in this research is qualitative with a phenomenological strategy. Data were collected through in-depth interviews with members of the DPRD in Tangerang City and the people of Tangerang City Electoral District I (Dapil I). The research shows that symbolic interaction occurs when giving directions and explanations related to recess activities to residents so that the community can understand the meaning of recess activities and can follow the directions given by the representative of residents and members of the council. In the end, symbolic interaction plays an important role in establishing a good relationship between Tangerang City DPRD members and their constituents. Kegiatan reses merupakan komunikasi verbal secara dua arah antara anggota legislatif dengan warga untuk menyerap aspirasi masyarakat secara langsung kepada anggota dewan tanpa perantara. Peneliti mengkaji interaksi simbolik dalam kegiatan reses yang diadakan oleh Anggota DPRD dan dihadiri oleh warga masyarakat. Teori ini membahas bagaimana pemikiran individu dalam suatu interaksi di lingkungan sosial. Terdapat mind, self, dan society dalam interaksi simbolik yang berperan penting dalam berlangsungnya interaksi sosial. Metodologi yang digunakan dalam penelitian ini adalah kualitatif dengan strategi fenomenologi. Pengumpulan data melalui wawancara mendalam dengan anggota DPRD Kota Tangerang dan masyarakat Dapil I Tangerang Kota. Penelitian menunjukkan interaksi simbolik terjadi saat pemberian arahan dan penjelasan terkait kegiatan Reses kepada warga sehingga masyarakat dapat memahami arti dari kegiatan Reses dan dapat mengikuti arahan yang diberikan oleh pihak warga dan anggota dewan. Pada akhirnya, interaksi simbolik berperan penting dalam menjalin hubungan yang baik antara Anggota DPRD Kota Tangerang dengan konstituennya.